Understanding History: Its Meaning and Essence - Ahmadin (Jurnal Ilmu Sosial dan Humaniora, 2022)
The recent emergence of various new approaches to study in the social sciences has resulted in the mixing of various scientific disciplines in their theoretical and methodological implementation. Thus, it is sometimes difficult for us to distinguish between one study of scientific disciplines and another, except to understand the scientific philosophy of each. In addition, history as a scientific discipline also experiences an increase in meaning in its learning, because history is only understood as limited to past events. This paper aims to explain various definitions of history, the purpose of studying history, and the essence of history. The benefits expected from reading this study are to gain an understanding of history conceptually and theoretically, especially for students and other parties interested in historical studies.